(untitled) (Applied Biological Research, 2020)
Tendu (Diospyros melanoxylon) leaf is used to wrap ‘Bidi’ or Indian cigarette due to its texture, flavour and workability. Experiments were conducted in tendu during 2015-2017 to assess the impact of pruning and application on chemical- and bio-fertilizers on leaf quality of this plant in Korba, Korea and Raipur districts of Chhattisgarh (India). Various levels of nitrogen (25-100 kg N ha-1) and phosphorus (250-1000g plot-1), neem granules, vesicular arbuscular mycorrhizal (VAM) and foliar spray of N and P (0.5-2.0%) were tested in a factorial randomized block design experiment. Every year pruning of tendu bushes of 2-4 cm girth at ground level increased the leaf surface area. Theapplication of 100 kg N ha-1 and 25 kg P ha-1to rhizosphere soil after rainy season improved tendu leaf quality in terms of specific leaf area. Foliar spray of 2% N and 1% P on tendu bushes enhanced leaf size and were more effective than chemical fertilizer application to soil. Similarly, application of biofertilizers in the form of 500 g neem granules and 1000 g VAM plot-1enhanced the leaf quality of tendu.